The bumpy road to the adoption of the Physical Internet – Overcoming barriers from a stakeholder perspective - Meyer, Tobias; Hartmann, Evi (6th International Physical Internet Conference Proceedings, 2019)
The Physical Internet aims for a paradigm shift by eliminating the unsustainability issues in today’s supply chain processes. The development of the concept in recent years has shown that the PI is still in its conceptualization phase. In order to increase the attention and adoption of the concept both, in literature and practice, empirical knowledge is needed concerning how and why affected stakeholders will adopt the concept. To address this gap, we gathered qualitative data through a single embedded case study approach. In total, we have integrated 14 stakeholders with verifiable expertise in the PI. The sample consists of logistics and transport service providers, shippers and includes companies selling or working on specific PI-products. Furthermore, we gathered empirical data from research institutes with specific knowledge or projects in the PI. This paper provides insights about the adoption of the PI and in particular about stakeholder intentions, organizational and technological readiness as well as barriers and drivers
Keywords: Physical Internet; Case Study; Open networks; Drivers